Integrasi Pengetahuan Konseptual Dan Praktis Dalam Sistem Akuntansi Modern: Peran SDM Dan Teknologi - Anwar Hidayat; Fitri Angguan; Heni Noviarita; Romlah (Kartika: Jurnal Studi Keislaman, 2025)
The digital transformation of the business environment requires accounting systems to dynamically adapt to changing conditions and increasingly complex informational demands. Modern accounting systems no longer function solely as transaction recording tools, but have evolved into managerial information systems that support strategic decision-making. This article integrates conceptual knowledge of basic accounting theories with the practical implementation of accounting systems, highlighting the critical roles of human resources (HR) and technology. A literature review approach is employed to examine contemporary developments in accrual-based accounting systems, Enterprise Resource Planning (ERP), and emerging technologies such as artificial intelligence (AI), blockchain, and cloud computing. Findings indicate that the effectiveness of modern accounting systems heavily depends on two key pillars: the digital literacy and competencies of accounting professionals, and the technological infrastructure that enables real-time data integration and process automation. The synergy between human capital and technology creates systems that are not only efficient but also responsive to regulatory requirements, transparency demands, and accountability standards. This study provides significant implications for educational institutions, practitioners, and policymakers in designing accounting curricula and HR development strategies aligned with the digital era